El cuerpo de la crisis. La ciudad y sus sintomatologías en el paisaje urbano - Carrasco Conde, Ana (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The article starts from the organic consideration of the city as body, which genesis goes back to Aristotle and is taken again on the Renaissance epoch by Francesco Patrizzi in La città felice (1553), to establish an analysis of the symptomatology of the crisis understood as disease (Cfr. R. Koselleck) in the urban fabric.
Keywords: city; crisis; body; Aristotle; Francesco Patrizzi; R. Koselleck